Expression of Glutathione peroxidase and Glutathione reductase and level of free radical processes under toxic hepatitis in rats - Iskusnykh, Igor Y. (2013)
Correlation between intensity of free radical processes estimated by biochemiluminesce parameters, content of lipoperoxidation products, and changes of glutathione peroxidase (GP, EC 1.11.1.9) and glutathione reductase (GR, EC 1.6.4.2) activities at rats liver injury, after 12, 36, 70, 96, 110, and 125 hours & tetrachloromethane administration have been investigated. The histological examination of the liver sections of rats showed that prominent hepatocytes with marked vacuolisation and inflammatory cells which were arranged around the necrotic tissue are more at 96 h after exposure to CCl4. Moreover maximum increase in GR and GP activities, 2.1 and 2.5 times, respectively, was observed at 96 h after exposure to CCl4, what coincided with the maximum of free radical oxidation processes. Using a combination of reverse transcription and real-time polymerase chain reaction, expression of the glutathione peroxidase and glutathione reductase genes (Gpx1 and Gsr) was analyzed by the determination of their respective mRNAs in the rat liver tissue under toxic hepatitis conditions. The analyses of Gpx1 and Gsr expression revealed that the transcript levels increased in 2.5- and 3.0-folds, respectively. Western blot analysis revealed that the amounts of hepatic Gpx1 and Gsr proteins increased considerably after CCl4 administration. It can be proposed that the overexpression of these enzymes could be a mechanism of enhancement of hepatocytes tolerance to oxidative stress.